2021
DOI: 10.3390/molecules26051294
|View full text |Cite
|
Sign up to set email alerts
|

Prodigiosin Sensitizes Sensitive and Resistant Urothelial Carcinoma Cells to Cisplatin Treatment

Abstract: Cisplatin-based treatment is the standard of care therapy for urothelial carcinomas. However, complex cisplatin resistance mechanisms limit the success of this approach. Both apoptosis and autophagy have been shown to contribute to this resistance. Prodigiosin, a secondary metabolite from various bacteria, exerts different biological activities including the modulation of these two cellular stress response pathways. We analyzed the effect of prodigiosin on protein levels of different autophagy- and apoptosis-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
3
13
0
1
Order By: Relevance
“…The combination also increased the expression of caspase-3, 8 and 9, inducing apoptosis and inhibiting adhesion of breast adenocarcinoma cell lines [MDA-MB-231 (15) ]. Similar effects were obtained with the association between prodigiosin and cisplatin, in which prodigiosin increased the sensitivity of cisplatin-resistant urothelial carcinoma cell lines (97) . Interestingly, despite being effective against a wide variety of cancer cells, prodigiosin has little, if any, cytotoxicity against normal cells (15,19,94) .…”
Section: Prodigininessupporting
confidence: 72%
“…The combination also increased the expression of caspase-3, 8 and 9, inducing apoptosis and inhibiting adhesion of breast adenocarcinoma cell lines [MDA-MB-231 (15) ]. Similar effects were obtained with the association between prodigiosin and cisplatin, in which prodigiosin increased the sensitivity of cisplatin-resistant urothelial carcinoma cell lines (97) . Interestingly, despite being effective against a wide variety of cancer cells, prodigiosin has little, if any, cytotoxicity against normal cells (15,19,94) .…”
Section: Prodigininessupporting
confidence: 72%
“…Montaner et al, (2000) earlier identified prodigiosin as an apoptotic agent. Several groups have replicated these findings using a variety of cancer cell lines (Montaner and Pérez-Tomás, 2001;Campàs et al, 2003;Perez-Tomas and Vinas, 2010;Dalili et al, 2012;Hassankhani et al, 2015;Berning et al, 2021). Currently, prodigiosin is in the preclinical phase for evaluation as an anti-cancer drug (Anwar et al, 2020).…”
Section: Introductionmentioning
confidence: 84%
“…An anticancer study demonstrated the effect of prodigiosin through tests with prostate cancer (PC3) and human choriocarcinoma (JEG3) cell lines in vitro and PC3 and JEG3 tumor-bearing nude mice in vivo, showing an inhibition of the proliferation and a reduction in the size and weight of the tumors, depending on the prodigiosin concentration and the treatment time, respectively [ 96 ]. Berning et al demonstrated that prodigiosin increases the sensitivity of cisplatin-resistant and sensitive urothelial carcinoma cell lines (RT-112) to cisplatin mediated by dysregulation of lysosomal function and reduction of cathepsin B and L activity [ 23 ]. Prodigiosin has great cytotoxic activity against many melanoma cancers cells lines, such as NGM, 501-Mel, WM293A, HT-144, SK-Mel-19, SK-Mel-28, and SK-Mel-147, showing mean IC 50 values of 0.2 µM through kinases modulation, intracellular acidification, DNA damage, and apoptosis induction [ 97 ].…”
Section: Biological Activity Of Prodigiosinmentioning
confidence: 99%
“…Prodigiosin is considered as the most important candidate for cancer treatment due to its low toxic effect over normal cells, and it has application as a natural colorant. Other possible applications that have recently emerged is the use of the molecule as a pH indicator, a UV ray protector, an autofluorescence product, and its application as a controlling agent in the formation of biofilm [ 16 , 22 , 23 , 24 , 25 , 26 ]. So far, the factors that have been identified that affect the production of prodigiosin are the type of microorganism, culture medium, incubation time, temperature, nitrogen, and phosphorus concentration, inorganic salts, and pH [ 15 , 20 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%